1990
DOI: 10.1007/bf00172086
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuity: an inbreeding avoidance mechanism in a socially monogamous species?

Abstract: Paternity likelihood was tested in a population of splendid fairy-wrens Malurus splendens by allozyme electrophoresis. A total of 91 offspring of 24 dams and 37 putative sires were typed at 10 polymorphic loci. All young were compatible with their dams but at least 65% were not fathered by any of the males in their group. A long-term study of this wren population has shown that the males are sedentary, show little evidence of dispersal and help care for the nestlings and fledglings in their group. Had the seni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
174
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(180 citation statements)
references
References 14 publications
5
174
1
Order By: Relevance
“…The specific conditions of the CIRMF colony represent an experimental setting, allowing the study of evolutionary phenomena that may have influenced mandrills in the wild. For example, past inbreeding depression may have led to the evolution of the incest avoidance mechanisms present in wild populations today (3,4). Finally, such restricted conditions may provide a useful model for populations undergoing habitat fragmentation in the wild (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific conditions of the CIRMF colony represent an experimental setting, allowing the study of evolutionary phenomena that may have influenced mandrills in the wild. For example, past inbreeding depression may have led to the evolution of the incest avoidance mechanisms present in wild populations today (3,4). Finally, such restricted conditions may provide a useful model for populations undergoing habitat fragmentation in the wild (53).…”
Section: Discussionmentioning
confidence: 99%
“…Inbreeding avoidance is thought to underlie the evolution of sex-biased dispersal (3,4) and has important implications for conservation (5).…”
mentioning
confidence: 99%
“…Absence of inbreeding avoidance or depression has been claimed from studies where pedigrees had been established on the basis of social partnerships only (e.g., Van Noordwijk and Scharloo 1981;Rowley et al 1986;Craig and Jamieson 1988;Gibbs and Grant 1989). In at least one case (the fairy wren, Malurus splendens), subsequent genetic analyses have shown that females are seeking extrapair copulations from unrelated males, who actually sire 65% or more of the offspring (Brooker et al 1990). In our study, pedigrees, relatedness, and inbreeding coefficient were established on the basis of genetic markers, which allowed us to verify that social partners were indeed the genetic contributors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, polyandry stimulates ovulation [6], ensures fertilization, or brings nuptial gifts [2]. Genetic beneits could be paternity choice [6]), sex ratio manipulation particularly in haplodiploid insects [7], inbreeding avoidance by mixed paternity [8], and sperm stored renewal [3].…”
Section: Introductionmentioning
confidence: 99%